REVIEW OF SPECIES OF KURZENKOTILLA LELEJ (MUTILLIDAE: MUTILLINAE) FROM INDIA - CHANDRAN, NITHYA; DEY, DEBJANI (The Bioscan, 2013)
Two species of the genus Kurzenkotilla Lelej (Mutillidae: Mutillinae: Mutillini) viz., species niveosignata André and scrobiculata Hammer are revised from India. The generic and species descriptions are updated through addition of taxonomic characters viz., shape, size, sculpture, setal orientation, morphometric ratios etc. These are supported by illustrations. In addition, annotated checklist and a key to the species are also provided.